Blockchain-based traceability system to support the Indonesian halal supply chain ecosystem - Andry Alamsyah; Naufal Hakim; Ratih Hendayani (Economies, 2022)
The halal industry is constantly developing into a broader concept of the Islamic economy, an economic activity that follows the Islamic-based principle. As a populous Muslim country, Indonesia follows the growth trend by aiming to dominate the global halal market. The strategy is to improve the current halal assurance process. Presently, the technology and procedure do not provide enough process transparency, traceability, and granularity of information. To achieve the strategic goal, a technological change is needed. A new emerging technology, blockchain, may potentially answer the challenge. This study's first objective is to discuss improving the current assurance practice in the Indonesian halal supply chain ecosystem, particularly in the meat industry. The second objective is to construct a traceability system model for the supply chain. Our goal is to propose a blockchain-based halal traceability system model. The model can be enhanced to be a national standard tool to develop the economy towards a sustainable supply chain.
Keywords: 330; blockchain; halal supply chain; slaughterhouse; traceability system